Effect of Lamination on Shale Reservoir Properties: Case Study of the Montney Formation, Canada - Juhwan Woo; Hyun Suk Lee; Carl Ozyer; Chul Woo Rhee (Geofluids)
The presence of lamination on sedimentary rocks is a distinct characteristic, particularly in shales. They are distinct due to the contrast between successive layers with regard to grain size, composition, color, and sedimentary structures, such as graded beds. Typically, the degree of lamination is controlled by the sedimentation rate and flow regime. Herein, we developed a mudstone classification scheme in terms of lamination because lamination-based shale facies are related to differing features in mineral composition, porosity, and Young’s modulus. This study also attempts to verify whether wireline log patterns are relevant to shale lithofacies. The relationship between the porosity and lamination of the Montney Formation can be used to estimate reservoir properties. Our results show that an increased silt lamina in mudstone leads to an increase in the quartz and calcite contents and a decrease in the clay content, which increases the porosity, permeability, and Young’s modulus. However, reservoir quality is not solely dependent on lamination because of the complex interaction between components. The degree of lamination affected the neutron, density, and sonic log responses. Furthermore, the presence of lamination tends to decrease the neutron percentage, with similar trends in density and sonic log box plots in the study area. When the percentage of clay or cement material decreases, the neutron and density log responses diminish. Meanwhile, when the rock texture variation increases with an increase in the degree of lamination, the sonic log response decreases.